2017
DOI: 10.1590/1982-0216201719313516
|View full text |Cite
|
Sign up to set email alerts
|

Alterações auditivas em crianças expostas à toxoplasmose durante a gestação

Abstract: RESUMO Objetivo: verificar a ocorrência e o tipo mais frequente de alteração auditiva em crianças expostas a toxoplasmose durante a gestação. Métodos: estudo retrospectivo longitudinal realizado em instituição pública de saúde de São Paulo. Análise de prontuários de crianças nascidas entre 2010 e 2015 distribuídos em dois grupos: grupo estudo, composto por 48 crianças de mães com diagnóstico de toxoplasmose durante a gestação; e grupo controle, composto por 43 crianças sem infecção congênita que foram acompanh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
1
0
2
Order By: Relevance
“…The poor adherence to the audiological monitoring (22%) in the population studied is worrisome, given the fact that chances of delayed-onset hearing impairment have been proven in the literature. The same was observed at the same institution that this study was conducted in a newborns toxoplasmosis monitoring (21) . Therefore, this could be related to the profile of the population assisted at the institution that mainly consists of people with low sociocultural level.…”
Section: Discussionsupporting
confidence: 69%
“…The poor adherence to the audiological monitoring (22%) in the population studied is worrisome, given the fact that chances of delayed-onset hearing impairment have been proven in the literature. The same was observed at the same institution that this study was conducted in a newborns toxoplasmosis monitoring (21) . Therefore, this could be related to the profile of the population assisted at the institution that mainly consists of people with low sociocultural level.…”
Section: Discussionsupporting
confidence: 69%
“…The authors report that the group of children with CT showed a statistically significant increase in the latency of V, A, E, F, and O and a decrease in the amplitude of the A and F waves ( Ferreira et al, 2020 ). Another interesting fact, when evaluating a group of children only exposed to toxoplasmosis during pregnancy, the authors observed that these children did not differ from the non-exposed group in terms of cochlear and conductive hearing loss, although they presented a higher occurrence of possible retrocochlear alteration ( Leite Filho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, a sincronia neural das estruturas auditivas em nível de tronco não se mostrou afetada em curto prazo pela exposição à sífilis materna, quando adequadamente tratada (20,21) .…”
Section: Discussionunclassified